THE PLACE(NESSLESS) OF PEDAGOGY AND DIDACTICS IN THE TEACHER TRAINING - Araújo, Osmar Hélio; Rodrigues, Janine Marta Coelho; Aragão, Wilson Honorato (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This article address to the relation that should exist between Pedagogy, Didactics and the teaching training of several areas of knowledge, whether initial or continuous, as it goes from the comprehension that curricular components that focus in the teaching know-how, the educational phenomena and the pedagogic practices are needed. For so, after considering researches and essays relevant to the subject and considering the aim of arguing about the place of Pedagogy and Didactics in the teacher training, the present article discuss the aspects that emerge in light of this topic, such as: the didactic-pedagogic teacher training; pedagogy as an educational science; didactics as a theoretic field of teaching; and, overall, to search to intercross pedagogy, didactics and teacher training. At last, it is highlighted that teacher training, most of the time, does not occur linked to pedagogy and, by so, that many teachers cannot build the needed pedagogical knowledges to the teaching profession. In the light of this ascertainment, this works ends reiterating the comprehension that it should exist a close relation between teacher training, pedagogy and didactics, as it is comprehended that these are inseparable fields.